The Influence of Work Motivation and Organizational Citizenship Behavior on the Performance of the West Java PDGI Management Board with Job Satisfaction as a Mediating Variable - Fiantini, Rosalina; Ariyani, Ida; Maharani, Anita (Universitas Sulawesi Barat, 2025)
The Influence of Work Motivation and Organizational Citizenship Behavior on the Performance of the West Java PDGI Management Board with Job Satisfaction as a Mediating Variable. This study investigates how work motivation and Organizational Citizenship Behavior (OCB) affect the performance of PDGI West Java board members, with job satisfaction as a mediating variable. Using a quantitative explanatory approach, data were collected from 186 board members across 23 branches through simple random sampling. A five-point Likert scale questionnaire was analyzed using SEM-PLS via SmartPLS. Findings show that work motivation (β = 0.573; t = 6.412; p < 0.001) and OCB (β = 0.315; t = 3.391; p = 0.001) significantly influence job satisfaction. However, job satisfaction does not significantly impact performance (β = 0.138; t = 1.594; p = 0.111) and fails to mediate the effect of motivation or OCB on performance. This implies that in a nonprofit professional setting like PDGI, performance is more directly shaped by intrinsic motivation and voluntary behavior than by job satisfaction. Strengthening intrinsic motivators, emphasizing non-material appreciation, and cultivating a culture of volunteerism are recommended to improve board performance